2017
DOI: 10.1057/bp.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical style and issue emphasis within the conference speeches of UKIP’s Nigel Farage 2010–2014

Abstract: Abstract:This paper makes a distinctive contribution to the academic literature on the United Kingdom Independence Party (UKIP) by focusing in on the political rhetoric of Nigel Farage in relation to his Conference speeches. Our first research question asks how his Conference speeches are constructed and delivered and identifies what rhetorical techniques are deployed to maximise their impact. In methodological terms we address this question through rhetorical political analysis (RPA). Our second research ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Perhaps not surprisingly, then, Crines and Heppell (2017), in their painstaking analysis of Farage’s party conference speeches between 2010 and 2014, find little to no evidence that the nature and scope of his rhetoric changed in response to external (and particularly economic) developments; although immigration became a more prominent feature of those speeches over time, it was all of a piece with a familiar, indeed predictable, appeal rooted in (British, non-European and non-immigrant) identity. In other words, the crises that may have pulled or pushed continental populist parties towards Euroscepticism merely served to reinforce a pre-fashioned fusion of anti-EU and anti-migration sentiment among British voters – especially those ‘left-behind’ by both cultural and much longer term economic change (Ford and Goodwin, 2014: 191–195; Goodwin and Milazzo, 2015: 78–100).…”
Section: Crisis: Confirmation Not Transformation Of Ukip’s Euroscepmentioning
confidence: 96%
“…Perhaps not surprisingly, then, Crines and Heppell (2017), in their painstaking analysis of Farage’s party conference speeches between 2010 and 2014, find little to no evidence that the nature and scope of his rhetoric changed in response to external (and particularly economic) developments; although immigration became a more prominent feature of those speeches over time, it was all of a piece with a familiar, indeed predictable, appeal rooted in (British, non-European and non-immigrant) identity. In other words, the crises that may have pulled or pushed continental populist parties towards Euroscepticism merely served to reinforce a pre-fashioned fusion of anti-EU and anti-migration sentiment among British voters – especially those ‘left-behind’ by both cultural and much longer term economic change (Ford and Goodwin, 2014: 191–195; Goodwin and Milazzo, 2015: 78–100).…”
Section: Crisis: Confirmation Not Transformation Of Ukip’s Euroscepmentioning
confidence: 96%
“…An interesting phenomenon that arose was the impression management of this context's main protagonists designed to cultivate feelings of familiarity: Alone the friendly term folks may seem fairly innocuous but considering this more widely, an image of Farage has been cultivated over the last 5 years of a man of the people who smokes and drinks at his local pub (Corcoran, 2018) so the informal usage of folks reinforces this image, creates a sense of familiarity and positions him as somebody trustworthy. The strategic use of persona by Farage was also identified by Crines and Heppell (2017) suggesting this attempt to create a positive self-identity is a common feature of his discourse. This informality is further demonstrable in the greetings used by contributors towards Farage:…”
Section: Cultivating Familiaritymentioning
confidence: 92%
“…In regard to gatekeeping, the role of the host, Nigel Farage, may influence the direction of the show, the participants chosen to take part and the discourse deemed appropriate for the context. Crines and Heppell’s (2017) analysis of the rhetorical features of Farage’s conference speeches from 2010 to 2014 found that his persuasive discourse was reliant on generating negative emotions ( pathos ) to draw support from the audience with references to an open-door immigration policy and its apparent connection to job losses and the impact on public services. His persona ( ethos ) was also prevalent through the use of humour and implicit references to his working life, emphasising an image of a hard-working, likeable character.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With his move into the leadership, as already noted, he instigated a shift in policy and presentation, while General Election campaign, when Lord Pearson struggled with both the media and the party, only served to underline Farage's value. As a highly charismatic individual (Crines and Heppell 2017), he was able to build a very significant media (and popular) following, as well as to overcome the ideological fissures that exist in the membership. In so doing, he has followed a path well-trodden by the Le Pens, Geert Wilders, Jörg Haider and many others in collapsing voters' conceptions of leader and party (see Taggart 1995;Weyland 2001).…”
Section: Ukip As An Outliermentioning
confidence: 99%